PREVALENSI PENYAKIT SCABIES PADA KAMBING LOKAL DI KECAMATAN WANARAYA KABUPATEN BARITO KUALA, PROVINSI KALIMANTAN SELATAN (Prevalence of Scabies Disease in Local Goats in Wanaraya District, Barito Kuala Regency, South Kalimantan Province) - Riyadhi, Muhammad; Herliani, Herliani; Mahdaniah, Nony Irma; Rizal, Muhammad; Syarifuddin, Nursyam Andi (Universitas Nusa Cendana, 2024)
Intensive goat farming without proper management poses a risk of disease spread, especially scabies. This study aims to determine the prevalence of scabies in Wanaraya District, Barito Kuala Regency. The research method is descriptive with samples taken from 38 selected goats out of a population of 282. The diagnosis of scabies was confirmed through two stages of examination: clinical symptoms and laboratory tests. Laboratory tests was conducted on skin scraping samples and microscopic examination revealed Sarcoptes scabiei mites in 18 samples. Prevalence was calculated by dividing the number of positive samples by the total number of samples and multiplying by 100%. The results showed that the prevalence of scabies in goats in Wanaraya District, Barito Kuala Regency was 6.38%.